PTU-073 Optimising treatment outcomes in chronic hepatitis C virus infection by improving treatment adherence rates. (23rd September 2015) - Campbell, L; Cook, N; Roguin, T; Marcinkowski, H; Tooley, V; Gellissen, R; Brown, A; Main, J; Thomas, H C; Thursz, M R
Abstract : Introduction: It is estimated that 250–500 000 people in the UK are infected with hepatitis C virus (HCV) making this one of the most important causes of liver-related morbidity and mortality. Standard of care (NICE recommended) treatment for chronic HCV infection is Pegylated interferon and Ribavirin for 24 or 48 weeks depending on the viral genotype. Pivotal studies of HCV genotype 1 (G1) infected patients treated for 48 weeks report a sustained virological response (SVR), (absence of viraemia 24 weeks after treatment completion) of 42–47%. Adherence to treatment, (defined as the number of treatment doses taken/number of treatment doses prescribed×100), is reported as 80%. We set out to determine whether improving patient adherence rates would increase SVR in patients with HCV genotype 1 infection. Methods: All patients considered suitable for treatment are referred by their consultant physician to a nurse led anti-viral service. Patients are counselled about treatment side effects, importance of adherence and virological targets. Each patient is given the opportunity to select their treatment start date to fit in around work or other commitments. Patients with a history of psychiatric disorder or with symptoms of depression are reviewed by a dedicated liaison psychiatrist. In the absence of clinical symptoms, neutrophil counts are allowed to drop to 0.4×109, haemoglobin to 8 g/dl and platelets to 60×109 before dose reductions were implemented. Twelve week stopping rules are applied for patients who do not achieve a 2 log10 drop in viral load. Adherence to therapy is monitored by patient reporting, counting residual medication and observing for inconsistencies in laboratory parameters. Results: 210 sequential G1 patients underwent treatment. 99% of patients rated quality of care as good or excellent. Adherence was 98%. SVR in G1 patients was 61% compared with 44% in published studies: P=0.001. In patients co-infected with HIV SVR rates were 65% compared to 40% in the Apricot study: P=0.01. Conclusion: Optimising patient adherence to treatment using a nurse led anti-viral service leads to a marked increase in treatment success rates.